Paul Bertagnolli, Prometheus in Music: Representations of the Myth in the Romantic Era (2007) - Byrne Bodley, Lorraine (Journal of the Society for Musicology in Ireland, 2010)
Review of Paul Bertagnolli, Prometheus in Music: Representations of the Myth in the Romantic Era (Burlington VT: Ashgate, 2007), ISBN 13–9780754654681